2013
DOI: 10.1007/s00253-013-4794-0
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic preparation of silybin phase II metabolites: sulfation using aryl sulfotransferase from rat liver

Abstract: Aryl sulfotransferase IV (AstIV) from rat liver was overexpressed in Escherichia coli and purified to homogeneity. Using the produced mammalian liver enzyme, sulfation-the Phase II conjugation reaction-of optically pure silybin diastereoisomers (silybin A and B) was tested. As a result, silybin B was sulfated yielding 20-O-silybin B sulfate, whereas silybin A was completely resistant to the sulfation reaction. Milligram-scale sulfation of silybin B was optimized employing resting E. coli cells producing AstIV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 35 publications
4
23
0
Order By: Relevance
“…In accordance with our previous study, efficient sulfation was only found for silybin B (up to 48%, Table 1) with the formation of silybin B 20- O -sulfate [18]. When silychristin or silydianin were tested as substrates in this AST IV catalyzed reaction, both consumption of the sulfate donor p -nitrophenyl sulfate ( p -NPS) and formation of p -nitrophenol ( p -NP) were observed (Table 1), which clearly proved the sulfation reactions.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In accordance with our previous study, efficient sulfation was only found for silybin B (up to 48%, Table 1) with the formation of silybin B 20- O -sulfate [18]. When silychristin or silydianin were tested as substrates in this AST IV catalyzed reaction, both consumption of the sulfate donor p -nitrophenyl sulfate ( p -NPS) and formation of p -nitrophenol ( p -NP) were observed (Table 1), which clearly proved the sulfation reactions.…”
Section: Resultssupporting
confidence: 92%
“…packed and eluted with 80% methanol. Only one sulfated product was obtained; silybin B 20- O -sulfate (14.5 mg, 0.03 mmol, yield 25%), whose identity was confirmed by comparison with previously published data [18]. …”
Section: Methodssupporting
confidence: 79%
See 3 more Smart Citations